Children’s literature in action : - Vardell, Sylvia M (Libraries Unlimited, 2008)
This book offers many activities and practical applications. Each chapter includes "Action" components that highlight literature, authors, specific book titles, or history. While varying in scope, these actions all help public librarians and school media specialists become familiar with the literature. This volume will build confidence in their ability to offer the best possible ways in which to link literature with active practices in school and public libraries and ultimately be able to find that "just right" book for their young patrons. It also includes evaluation criteria, writing reviews, collection development of various genres, awards, and other programs of merit as well as additional information in numerous bibliographies and lists of recommended reading and Web sites.